Analisis Data Panel Untuk Menguji Pengaruh Estimasi Biaya Produksi Terhadap Harga Jual pada Workshop PT Multi Karya Bajatama - Elvianto Elvianto; Dwi Kartikasari (Politeknik Negeri Batam, 2015)
This study aimed to analyze the estimated cost of production to the selling price, and want to know the suitability costing companies with existing theories. Data were collected from PT Multi Karya Bajatama by sampling method, totals of samples used were 169, data were collected from June to December 2014. This study uses panel data analysis with the model common effect and fixed effect. The study found that the cost of production significantly influence the selling price. Having compared the way costing companies with existing theory, getting the less fit. Researchers suggest, should the company change the calculation of the estimated cost of production.